2021
DOI: 10.1101/2021.05.17.21256513
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Japan COVID-19 Task Force: a nation-wide consortium to elucidate host genetics of COVID-19 pandemic in Japan

Abstract: To elucidate the host genetic loci affecting severity of SARS-CoV-2 infection, or Coronavirus disease 2019 (COVID-19), is an emerging issue in the face of the current devastating pandemic. Here, we report a genome-wide association study (GWAS) of COVID-19 in a Japanese population led by the Japan COVID-19 Task Force, as one of the initial discovery GWAS studies performed on a non-European population. Enrolling a total of 2,393 cases and 3,289 controls, we not only replicated previously reported COVID-19 risk … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“… 79 , 100 There is one Mendelian randomization study in an East Asian population that also showed a detrimental effect of obesity in severe COVID-19. 88 Others identified new determinants including increased testosterone, 96 and reduced carnitine and acetyl-carnitine 84 was associated with higher risk of COVID-19 severity and hospitalization, respectively. The updated GWAS of COVID-19 HGI included assessment of a wide range of exposures in COVID-19 risk and highlighted increased liability of type 2 diabetes associated with higher risk of COVID-19 susceptibility and hospitalization, although the association was abolished after adjusting for BMI.…”
Section: Resultsmentioning
confidence: 99%
“… 79 , 100 There is one Mendelian randomization study in an East Asian population that also showed a detrimental effect of obesity in severe COVID-19. 88 Others identified new determinants including increased testosterone, 96 and reduced carnitine and acetyl-carnitine 84 was associated with higher risk of COVID-19 severity and hospitalization, respectively. The updated GWAS of COVID-19 HGI included assessment of a wide range of exposures in COVID-19 risk and highlighted increased liability of type 2 diabetes associated with higher risk of COVID-19 susceptibility and hospitalization, although the association was abolished after adjusting for BMI.…”
Section: Resultsmentioning
confidence: 99%
“…In this retrospective cohort study, all COVID-19 cases were recruited through the Japan COVID-19 Task Force. 15 From February 2020 to October 2021, data from consecutive patients aged ≥ 18 years who were diagnosed with COVID-19 based on polymerase chain reaction or antigen test and who agreed to participate in the study were entered into an electronic case record form by the attending physicians at the a liated research institutions. We excluded patients who met any of the following exclusion criteria: (i) non-Japanese patients, (ii) patients with incomplete medical records, for example, insu cient data to extract critical outcome information, and (iii) patients for whom genome-wide association study (GWAS) genotyping data were not available (Figure 1).…”
Section: Study Design and Settingsmentioning
confidence: 99%
“…We applied stringent quality control (QC) lters to the samples and variants, as described in a previous study. 15 A total of 2,433 COVID-19 cases passed sample QC. Subsequently, we performed genome-wide genotype imputation; the details are described in a previous study.…”
Section: Genotype Data Of Covid-19 Patientsmentioning
confidence: 99%
See 2 more Smart Citations